Global age-friendly cities : a guide. (World Health Organization, 2007)
Population aging and urbanization are major forces shaping the 21st century. As cities are growing, their share of residents aged 60 years and more is increasing. WHO regards active aging as a lifelong process shaped by several factors that, alone and acting together, favor health, participation and security in older adult life. The purpose of this guide is to engage cities to become more age-friendly so as to tap the potential that older people represent for humanity. Working with groups in 33 cities, WHO asked older people in focus groups to describe the advantages and barriers they experience in eight areas of city living. In most cities, the reports from older people were complemented by evidence from focus groups of caregivers and service providers in the public, voluntary and private sectors. The results from the focus groups led to the development of a this set of age-friendly city checklists. The cities surveyed were: Amman, Jordan; Cancún, Mexico; Dundalk, Ireland; Geneva, Switzerland; Halifax, Canada; Himeji, Japan; Islamabad, Pakistan; Istanbul, Turkey; Kingston and Montego Bay (combined); Jamaica La Plata, Argentina; London, United Kingdom; Mayaguez, Puerto Rico; Melbourne, Australia; Melville, Australia; Mexico City, Mexico; Moscow, Russian Federation; Nairobi, Kenya; New Delhi, India; Ponce, Puerto Rico; Portage la Prairie, Canada; Portland, Oregon, United States of America; Rio de Janeiro, Brazil; Ruhr metropolitan region, Germany; Saanich, Canada; San José, Costa Rica; Shanghai, China; Sherbrooke, Canada; Tokyo, Japan; Tripoli, Lebanon; Tuymazy, Russian Federation; Udaipur, India; Udine, Italy--Publisher's description.